Stigmatisasi Pengguna Media Sosial Pada Perempuan Bertato Studi Pada Akun Instagram @Nathalieholscher - Hanifah Abidah; Rini Sulastri (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to describe women and Instagram social media and to explore and understand more about stigma that arise against tattooed women in the comments of @nathalieholscher's Instagram account. Women actively use Instagram to convey emotions, express themselves, and share aspects of their daily lives. A video post on @nathalieholscher's Instagram account featuring a tattoo on her arm received many disapproving comments and created a negative stigma. The relevant stigma in this case includes negative comments towards women with tattoos. To examine the phenomenon of stigma towards women with tattoos, this research uses the theory proposed by Eving Goffman regarding the components of stigma consisting of labelling, stereotyping, separation, and discrimination. This study uses a qualitative research method with the type and approach of content analysis which is focused on tracing and analyzing the comments of Instagram social media users. The results of this study show that women, especially those with tattoos, need to be wise in managing their use of social media to avoid negative stigma. In the upload of the Instagram account @Nathalieholscher showing off the tattoos on her arms triggered a negative response which included the stigma components of labeling found 9 (nine) data, stereotyping 3 (three) data, separation 3 (three) data, and discrimination 5 (five) data.